Research Trend of Local Wisdom Issues Based on Scopus Journal Database: A Bibliometric Study - Ni Nyoman Sri Putu Verawati; Agus Ramdani (Postgraduate Program, University of Mataram, 2023)
This bibliometric study delves into the multifaceted dimensions of local wisdom research based on an exhaustive analysis of scholarly publications indexed in the Scopus Journal Database. Focused on the intersection of local wisdom with education and learning, the study employs a comprehensive methodology encompassing data collection, bibliometric analysis, visualization techniques, geographical analysis, and quality assurance measures. The findings, derived from the systematic examination of 4,268 documents spanning nearly a century, reveal the evolution, contributors, and global patterns within the field. Notably, the analysis of 45 selected journal articles provides a nuanced understanding of the diverse applications of local wisdom, ranging from teacher responsibility and multicultural harmony to conservation management and innovative learning models. The robust citation counts of key studies underscore the substantial impact of local wisdom in shaping educational practices and fostering holistic development. Geographically, Indonesia emerges as a central hub of local wisdom research, with Indonesian researchers playing a pivotal role and actively engaging in international collaborations. In conclusion, this comprehensive overview not only contributes valuable insights to the ongoing discourse on local wisdom but also provides a foundation for future research endeavors, emphasizing the critical role of local wisdom in addressing global challenges and fostering sustainable solutions, particularly in the realm of education.